Imaging of the Lamina Cribrosa in Glaucoma: Perspectives of Pathogenesis and Clinical Applications*. (11th June 2013) - Kim, Tae-Woo; Kagemann, Larry; Girard, Michaël J. A.; Strouthidis, Nicholas G.; Sung, Kyung Rim; Leung, Christopher K.; Schuman, Joel S.; Wollstein, Gadi
Abstract: The lamina cribrosa (LC) is a sieve-like structure in the sclera where retinal ganglion cell axons exit from the eye. The LC has been known to play a critical role in the pathogenesis of glaucoma. With the advent of imaging technologies, such as enhanced depth imaging, spectral-domain optical coherence tomography (OCT) enables us to unveil the LC in vivo features. The application of adaptive optics technology and a compensatory image-processing algorithm has further improved the visualization of the beams and pores and neural pathways of the LC and the scleral insertion sites. Monitoring the changes of these structures in relation to acute and chronic elevation of intraocular pressure would be germane to decipher the relationship between the stress and strain response of the LC and optic nerve damage and improve our understanding of glaucoma pathophysiology. While the impact of investigating the integrity of LC is substantive, considerable challenges remain for imaging the LC. Nevertheless, with the rapid development of the OCT technology, it is expected that some of these limitations can be overcome and the potentials of LC imaging will be unraveled.